REFLECȚII ASUPRA INTERPRETĂRII NOȚIUNILOR DE „FOLOSIREA FORȚEI” „ATAC ARMAT”ȘI „ACT DE AGRESIUNE” - Gherega, Carolina (ВЕРХОВЕНСТВО ПРАВА, 2017)
The studyfocuses on the brief analysis of the notions of «use of force», «armed attack» and «act of aggression». The aim is to elucidate the meaning of these concepts for the correct interpretation of the principle of non-refoulement to force and threats of force in international relations.